Number of replicates in trials for evaluating melon hybrids - Bezerra Araújo Junior, Bernardo; Ferreira Martins, Adriano; Welk Lopes Pereira Nunes, Elaíne; Bezerra de Melo, Stefeson; Henrique de Sousa Nunes, Glauber (Revista Ciência Agronômica, 2023)
During experiment planning, determining the number of replicates for tested treatments is important because it directly affects the accuracy of the obtained results. This study was conducted to determine the number of measurements (repetitions) necessary to evaluate the yield traits and soluble solids in Cantaloupe and Gália melon hybrid trials. The study comprised twenty-one experiments, nine for evaluating eight Cantaloupe melon hybrids, and twelve for evaluating nine Galia melon hybrids, conducted in a randomized complete block design with three replicates each. Analysis of variance was performed, and repeatability and genotypic determination coefficients were estimated for each experiment. The use of three repetitions allowed identification of superior genotypes with 83.6 and 80.7% predictions of the real values for the yield and soluble solids, respectively, for Cantaloupe melons. Evaluating the trials with Galia melon using three repetitions allowed prediction of the true value of the genotypes with 86.1 and 98.6% accuracy for fruit yield and soluble solids, respectively. Therefore, the use of three replicates was determined to be sufficient for detecting superior genotypes both for fruit yield and soluble solid content, with more than 80% certainty for their true values.